Intraprotein electron transfer between tyrosine and tryptophan in DNA photolyase from Anacystis nidulans - Aubert, Corinne (The National Academy of Sciences, 1999)
Light-induced electron transfer reactions leading to the fully reduced, catalytically competent state of the flavin adenine dinucleotide (FAD) cofactor have been studied by flash absorption spectroscopy in DNA photolyase from Anacystis nidulans. The protein, overproduced in Escherichia coli, was devoid of the antenna cofactor, and the FAD chromophore was present in the semireduced form, FADH(⋅), which is inactive for DNA repair. We show that after selective excitation of FADH(⋅) by a 7-ns laser flash, fully reduced FAD (FADH(−)) is formed in less than 500 ns by electron abstraction from a tryptophan residue. Subsequently, a tyrosine residue is oxidized by the tryptophanyl radical with t([Formula: see text]) = 50 μs. The amino acid radicals were identified by their characteristic absorption spectra, with maxima at 520 nm for Trp(⋅) and 410 nm for TyrO(⋅). The newly discovered electron transfer between tyrosine and tryptophan occurred for ≈40% of the tryptophanyl radicals, whereas 60% decayed by charge recombination with FADH(−) (t([Formula: see text]) = 1 ms). The tyrosyl radical can also recombine with FADH(−) but at a much slower rate (t([Formula: see text]) = 76 ms) than Trp(⋅). In the presence of an external electron donor, however, TyrO(⋅) is rereduced efficiently in a bimolecular reaction that leaves FAD in the fully reduced state FADH(−). These results show that electron transfer from tyrosine to Trp(⋅) is an essential step in the process leading to the active form of photolyase. They provide direct evidence that electron transfer between tyrosine and tryptophan occurs in a native biological reaction.